Effectiveness of a Computer Game for Recognizing and Understanding Facial Emotions in Hearing-Impaired Children - Ghanat, Mozhgan; Zaraii Zavaraki, Esmaeil; Jafarkhani, Fatemeh; Bakhtiarvand, Morteza (Revija za elementarno izobraževanje, 2025)
The present study evaluates the effectiveness of the EMOFIT computer game on the recognition and understanding of facially expressed emotions in 6-10-year-old hearing-impaired children. This quasi-experimental, pre-test-post-test design study, with control and experimental groups, was conducted with the participation of thirty children. The results showed significant improvement in emotion understanding, especially in adaptation (e.g., η² = 0.84), with slight improvement in naming (e.g., η² = 0.57). Results suggest that games like EMOFIT can effectively improve impaired social skills and emotional development among children.
Keywords: Computer Game, Facial Emotion Recognition, Facial Emotion Understanding, Hearing Impairments.